Maternal Reading History Predicts Neural Activity During Phonological Processing in Pre-readers - Kaminski, Adam M. (Tufts Archival Research Center, 2017)
AbstractReading ability, particularly reading impairment, tends to run in families. Models of developmental disorders, such as the Multiple Deficit Model (MDM) and intergenerational MDM (iMDM), account for such intergenerational transfer by highlighting diverse genetic and environmental pathways that affect diverse underlying etiologies. More research should be done in order to elucidate 1) the extent to which genetic and environmental pathways are at play in the intergenerational transfer of reading ability, 2) the specific neural mechanisms that underlie such transfer, and 3) the individual impact of mothers versus fathers. Aiming at these points, the present study investigated the neural activity of pre-readers (aged 60-80 months) during a phonological processing task in relation to a self-report assessment of parental reading history. Environmental and cognitive variables were controlled for in an attempt to measure the direct effect of genetic pathways from parents to children. Results revealed that maternal, but not paternal, reading history predicted neural activity in four brain regions during phonological processing. These were the lingual gyrus, the left parietotemporal gyrus, the left occipitotemporal gyrus, and the right middle temporal gyrus. Reading-adept mothers tended to have children with greater activation during phonological processing in these regions. The intergenerational transfer of reading ability is likely, in part, genetic, and the implicated brain regions may constitute some of the neural mechanisms by which reading ability is conferred genetically. Furthermore, in the present study, maternal genes seemed to have more influence than paternal ones in shaping reading development via the neural mechanisms supportive of phonological processing. Keywords: Phonological processing, ARHQ, fMRI, intergenerational transfer